2021
DOI: 10.1038/s41386-021-01097-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to alcohol use disorder treatment outcomes: a genome-wide pharmacogenomics study

Abstract: Naltrexone can aid in reducing alcohol consumption, while acamprosate supports abstinence; however, not all patients with alcohol use disorder (AUD) benefit from these treatments. Here we present the first genome-wide association study of AUD treatment outcomes based on data from the COMBINE and PREDICT studies of acamprosate and naltrexone, and the Mayo Clinic CITA study of acamprosate. Primary analyses focused on treatment outcomes regardless of pharmacological intervention and were followed by drug-stratifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 59 publications
1
37
0
1
Order By: Relevance
“…This research strategy has been used repeatedly to generate and test genomic and pharmacogenomic hypotheses and has proven to be a powerful research tool for identifying novel biology [ 9 , [24] , [25] , [26] ]. Specifically, we previously recruited 442 subjects with AUD for an acamprosate clinical trial ( Table 1 ) [ 27 ]. Alcohol consumption was measured by self-report using Timeline Followback (TLFB).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research strategy has been used repeatedly to generate and test genomic and pharmacogenomic hypotheses and has proven to be a powerful research tool for identifying novel biology [ 9 , [24] , [25] , [26] ]. Specifically, we previously recruited 442 subjects with AUD for an acamprosate clinical trial ( Table 1 ) [ 27 ]. Alcohol consumption was measured by self-report using Timeline Followback (TLFB).…”
Section: Resultsmentioning
confidence: 99%
“…The genomic dataset was derived from the Mayo Clinic Center for the Individualized Treatment of Alcoholism Study, as described previously [ 8 ]. Genome-wide associations between genetic variants and plasma FGF21 levels were examined using linear regression, adjusted for sex, age, and study site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously conducted an acamprosate clinical trial to identify potential biomarkers associated with acamprosate treatment response using metabolomics and genomics ( Hinton et al, 2017 ; Ho et al, 2020 ; Biernacka et al, 2021 ). Those AUD patients were treated with acamprosate for 3 months in community-based treatment programs ( Karpyak et al, 2014 ; Karpyak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those AUD patients were treated with acamprosate for 3 months in community-based treatment programs ( Karpyak et al, 2014 ; Karpyak et al, 2019 ). The primary outcome was abstinence, but we also collected comprehensive clinical information for this study cohort before and after 3 months of acamprosate treatment ( Karpyak et al, 2019 ; Biernacka et al, 2021 ). Our previous study suggested that genetic variants in the TSPAN5 gene were associated with acamprosate treatment response ( Ho et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%